ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN DI INDONESIA (STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2015 - 2016) - Teresa Avilla Adine Utama; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2022)
This research aims to verify the factors that effect on company dividend policy in Indonesia. The independent variables in this research are corporate governance, firm size, profitability of the company, and company's growth. Meanwhile, the dependent variable in this research is dividend policy. This research uses secondary datas from financial report and annual report that are registered in Indonesian Stock Exchange by using purposive sampling method. The samples chosen are all companies that published their financial report and annual report, also provided datas about corporate governance, firm size, company's profitability, and company's growth in 2015-2016. This research uses multiple regression analysis method.The result of this research shows that corporate governance, firm size, and company's profitability give positive impacts to dividend policy. Meanwhile, company's growth gives negative impacts to dividend policy.